Innovation and pre-approval in the public sector: examples from GCHQ and Buurtzorg - Stewart, Henry (Henry Stewart Talks, 2019)
This case study examines two public sector organisations, GCHQ and Buurtzorg, to explore how pre-approval is reducing bureaucracy, increasing the speed of change, and saving money.